1984
DOI: 10.1038/clpt.1984.256
|View full text |Cite
|
Sign up to set email alerts
|

Mephenytoin hydroxylation deficiency in Caucasians: Frequency of a new oxidative drug metabolism polymorphism

Abstract: The ability of normal subjects to hydroxylate mephenytoin (100 mg) or debrisoquine (10 mg) after oral dosing was investigated in 156 unrelated Caucasians living in middle Tennessee. Urinary recovery of 4-hydroxymephenytoin (4-OH-M) and the urinary S:R enantiomeric ratio of mephenytoin measured in an 8-hr urine sample were investigated as phenotypic traits for mephenytoin, and the urinary metabolic ratio of debrisoquine was used to determine the debrisoquine hydroxylase phenotype. Both urinary 4-OH-M and the S:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
4
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(153 citation statements)
references
References 12 publications
7
141
4
1
Order By: Relevance
“…42,45 Now these results can be clearly explained by interethnic variations in the CYP2C19 genotype. Among North American and European populations, 56.7-81.0% of patients are homo-EMs, 18.0-37.2% are hetero-EMs, and PMs are less than 6.1%, [46][47][48][49][50] and thus omeprazole 40 mg is required to achieve stronger gastric acid suppression than H 2 -RAs. However, in Orientals, homo-EMs are only 27.7-38.2% and the rest of the population has an intermediate or reduced capacity to metabolize omeprazole; 30,[51][52][53] and therefore strong gastric acid suppression can be obtained even with omeprazole 20 mg or less.…”
Section: Discussionmentioning
confidence: 99%
“…42,45 Now these results can be clearly explained by interethnic variations in the CYP2C19 genotype. Among North American and European populations, 56.7-81.0% of patients are homo-EMs, 18.0-37.2% are hetero-EMs, and PMs are less than 6.1%, [46][47][48][49][50] and thus omeprazole 40 mg is required to achieve stronger gastric acid suppression than H 2 -RAs. However, in Orientals, homo-EMs are only 27.7-38.2% and the rest of the population has an intermediate or reduced capacity to metabolize omeprazole; 30,[51][52][53] and therefore strong gastric acid suppression can be obtained even with omeprazole 20 mg or less.…”
Section: Discussionmentioning
confidence: 99%
“…A debrisoquine test to determine the CYP2D6 phenotype was performed following the method by Wedlund et al (10). Oxymorphone was analyzed by G.C.…”
Section: Study Protocolmentioning
confidence: 99%
“…The human CYP2C subfamily consists of at least 4 members (CYP2C8, CYP2C9, CYP2C18, CYP2C19) [1,2]. Extensive metabolizer (EM) and poor metabolizer (PM) polymorphism for mephenytoin [3,4] is well known and has been studied extensively. It has been shown that CYP2C19 is a candidate for mephenytoin 4'-hydroxylation [5,6].…”
Section: Introductionmentioning
confidence: 99%